Truth as functionality: what scientific practice teaches us about truth? - Orozco C., Richard Antonio (2019)
In this paper, the author presents an explanation of the truth that is obtained from scientific practice. In this way, truth is revealed as functionality, but functionality is understood as negotiation between the researcher, the community and the researched world. However, the author also finds the need not to close the explanation of the truth in a single answer; and that is why he presents a pluralistic explanation of truth that conceives functionality as crosses all the others, and thus accepting that. There are other ways to explain the truth.